2011
DOI: 10.1115/1.4005136
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mixing Using Side Port Air Injection on a Biomass Fluidized Bed

Abstract: Fluidized beds are being used in practice to gasify biomass to create producer gas, a flammable gas that can be used for process heating. However, recent literature has identified the need to better understand and characterize biomass fluidization hydrodynamics, and has motivated the combined experimental-numerical effort in this work. A cylindrical reactor is considered and a side port is introduced to inject air and promote mixing within the bed. Comparisons between the computational fluid dynamics (CFD) sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Deza et al studied the effect of side port air flow on particle mixing in a biomass fluidized bed having similar dimensions as previously referenced. 31 Drake and Heindel applied the 3D X-ray computed tomography to determine local time averaged gas holdup in fluidized beds with side air injection considering scale-up of such devices. 32 Min et al compared the computational fluid dynamics simulation to the experimental data of a laboratory scale fluidized bed with and without side gas injection.…”
Section: Introductionmentioning
confidence: 99%
“…Deza et al studied the effect of side port air flow on particle mixing in a biomass fluidized bed having similar dimensions as previously referenced. 31 Drake and Heindel applied the 3D X-ray computed tomography to determine local time averaged gas holdup in fluidized beds with side air injection considering scale-up of such devices. 32 Min et al compared the computational fluid dynamics simulation to the experimental data of a laboratory scale fluidized bed with and without side gas injection.…”
Section: Introductionmentioning
confidence: 99%
“…The use of CFD to model fluidized beds is highly dependent on the boundary conditions and validation through experimentation. Deza et al [8,9] and Min et al [10] have shown that X-ray visualization techniques can be used as a validation tool for fluidized bed hydrodynamic simulations.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of biomass [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64], Luo et al [50] estimated the annual generation of crop residues, animal manure and organic faction of MSW in Hebei Province, China from 2002 to 2007. Qiao et al [51] investigated the biogas recovery from microwave heated sludge by anaerobic digestion.…”
Section: Biomass Energymentioning
confidence: 99%